APLIKASI PRESENSI DENGAN BARCODE SCANNER DAN RASPBERRY PI TERINTEGRASI BOT TELEGRAM - Ana Soraya; Eko Riyanto; - Solikhin (Universitas PGRI Semarang, 2020)
In this research, the presence of students' attendance at the Taruna Bulu Vocational School has been observed where the system used is still manual so it requires a computerized system so that archiving is efficient and the homeroom teacher and student guardian can control student attendance.In conducting research, the author uses two sources of data, namely primary data which includes all data obtained by the author directly from sources obtained from the Head of Vocational School Hair Training and secondary data which includes all information obtained from other data that can be used as a support and related to the research theme. These data sources are documents concerning the student attendance information system procedures. In designing the system, it is made based on the needs of SMK Taruna Bulu which is then implemented using the PHP My SQL programming language and integrated Telegram Bot so that it can later be implemented on Taruna Bulu Vocational School.